Reversed Phase High-Performance Liquid Chromatographic Ultra-violet (Photo Diode Array) Quantification of Oleanolic Acid and its Isomer Ursolic Acid for Phytochemical Comparison and Pharmacological Evaluation of Four Leucas Species Used in Ayurveda - Shukla, Pushpendra Kumar (Pharmacogn Mag, 2016)
CONTENT: Different Leucas species are well known as “Dronpushpi,” a well-known herb of Ayurveda, used in the treatment of various ailments. OBJECTIVE: Evaluation of four industrially important Leucas species for their in vitro antidiabetic potential and radical scavenging effect along with high-performance liquid chromatographic quantification of the bioactive triterpenes. MATERIALS AND METHODS: The quantification of triterpenes was carried out on C-18 column with acetonitrile and water (90:10) as the solvent system at a detection wavelength of 210 nm. In vitro antidiabetic activity was evaluated by α-amylase inhibition assay based on starch–iodine and 3,5 dinitrosalicylic acid (DNS) method. Antioxidant activity was calculated by five different models, namely total phenolic and total flavonoid content, free radical scavenging activity by 1-1-diphenyl-2-pic-rylhydrazyl (DPPH), ferric-reducing power assay, and the total antioxidant capacity. RESULTS: Maximum concentration of oleanolic acid was found in Leucas cristata, followed by Leucas mollissima, Leucas Aspera, and Leucas biflora. Ursolic acid was highest in L. mollissima and then in L. biflora, L. cristata, and L. aspera, respectively. In in vitro antidiabetic activity, IC(50) of L. aspera (1.56 ± 0.01 mg/ml) and L. mollissima (0.75 ± 0.005 mg/ml) were found to be highest in DNS and iodine starch assay. IC(50) in DPPH assay ranges from 0.6 ± 0.011 to 1.68 ± 0.011 mg/ml. Antioxidant capacity follows the order; L. aspera > L. mollissima > L. biflora > L. cristata. CONCLUSION: Promising activities were observed in targeted species, thus L. mollissima, L. biflora, and L. cristata can be used alternatively as a substitute to L. aspera. SUMMARY: Physicochemical parameters are within the limit as per the Ayurvedic Pharmacopoeia of India. Maximum concentration of oleanolic acid was found in Leucas cristata; however, ursolic acid was highest in Leucas mollissima. In vitro antidiabetic activity of Leucas aspera and L. mollissima was found to be heighest as compared to other species. However, antioxidant capacity is almost similar in targeted species. Promising activities were observed in all the species, thus L. mollissima, Leucas biflora, and L. cristata can be used alternatively as a substitute to L. aspera.